Ethnic Inequality - Alesina, Alberto; Michalopoulos, Stelios; Papaioannou, Elias (The Journal of political economy, 2016)
This study explores the consequences and origins of between-ethnicity economic inequality across countries. First, combining satellite images of nighttime luminosity with the historical homelands of ethnolinguistic groups we construct measures of ethnic inequality for a large sample of countries. We also compile proxies of overall spatial inequality and regional inequality across administrative units. Second, we uncover a strong negative association between ethnic inequality and contemporary comparative development; the correlation is also present when we condition on regional inequality, which is itself related to under-development. Third, we investigate the roots of ethnic inequality and establish that differences in geographic endowments across ethnic homelands explain a sizable fraction of the observed variation in economic disparities across groups. Fourth, we show that ethnic-specific inequality in geographic endowments is also linked to under-development.